Praktik Adat Kekampi Desa Pagar Agung Muara Enim dan Akibat Hukumnya Menurut Hukum Keluarga Islam - Ifrohati, Ifrohati; Ramelan, Rafida; Halnasia, Rati (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The purpose of the research is to find out the implementation of kekampi customs and a review of Islamic family law on kekampi customs in the village. The method used in this study is field research or qualitative (field research) collecting data directly dealing with the phenomena that occur data, namely by interview and documentation. Data analysis techniques use descriptive analysis by presenting the results of interviews and drawing conclusions deductively. The results of the study obtained are that the practice of the kekampi custom consists of several stages, namely the first is the arrival of the prospective groom, the second is the arrival of the prospective groom with his family, the third is the arrival of the woman's family to the groom's house, the fourth is gathering the family, the fifth is the cooking event and the arrival of residents, the sixth is the marriage contract, the seventh is the reception. And the legal consequences of the agreement between the two parties who carry out the kekampi custom are regarding property, residence, inheritance, and the position of the man. Therefore, Islamic law states that the marriage of kekampi custom is a custom that is not prohibited in Islamic law, but looking at the incompatibility of the legal consequences of kekampi custom, it is not in accordance with Islamic law. For this reason, kekampi custom marriage can be said to be corrupt because kekampi custom is a customary custom in which there are legal consequences in terms of property, inheritance and the position of the man that is not in line with Shari'ah.